How Does Employee–Organization Relationship Affect Work Engagement and Work Well-Being of Knowledge-Based Employees? - Che, Yi; Zhu, Jian; Huang, Huawei (Frontiers in Psychology, 2022)
In the employment relationship, organizational factors are the main factors that affect employee behavior. Especially for knowledge-based workers, it is even more crucial for organizations to give enough attention to their individual needs. Based on Existence, Relatedness, and Growth (ERG) theory, this study constructs a moderated mediating model to explore how the impact of the employee–organization relationship (EOR) on work engagement (WE) and work well-being (WWB) of knowledge-based employees. In this study, existence–relatedness–growth need satisfaction (GNS) is used as a mediator and the perceived symbiotic relationship is used as a moderator. Data collected from 791 knowledge-based employees in higher education institutions from more than 20 provinces and cities in China are used to test the model. The results show that (1) EOR has significant positive effects on WE and WWB. (2) Need satisfaction for relatedness partially mediates the effects of EOR on WE and WWB. (3) Need satisfaction for growth mediates the effect of EOR on WE while the mediating role of need satisfaction for growth between EOR and WWB is unsupported. (4) The mediating role of need satisfaction for the existence of EOR on both WE and WWB is unsupported. (5) The perceived symbiotic relationship moderates the relationship between EOR and WE and WWB. The findings are of theoretical significance in expanding the research field of EOR and providing a basis for organizations to implement EOR strategies.